Memory and eye movement desensitization and reprocessing therapy: a potentially risky combination in the courtroom - Otgaar, Henry; Houben, Sanne T. L.; Rassin, Eric; Merckelbach, Harald (Memory (Hove), 2021)
Does Eye Movement and Desensitization and Reprocessing (EMDR) therapy affect the accuracy of memories? This recurrent issue in recent memory research bears relevance to expert witness work in the courtroom. In this review, we will argue that several crucial aspects of EMDR may be detrimental to memory. First, research has shown that eye movements undermine the quality and quantity of memory. Specifically, eye movements have been shown to decrease the vividness and emotionality of autobiographical experiences and amplify spontaneous false memory levels. Second, a sizeable proportion of EMDR practitioners endorse the controversial idea of repressed memories and discuss the topic of repressed memory in therapy. Third, in the Dutch EMDR protocol, patients are instructed to select the target image by using flawed metaphors of memory (e.g., memory works as a video). Such instructions may create demand characteristics to the effect that people over-interpret imagery during therapy as veridical memories. Collectively, the corpus of research suggests that several components of EMDR therapy (i.e., performing eye movements, therapist beliefs and therapeutic instructions) may undermine the accuracy of memory, which can be risky if patients, later on, serve as witnesses in legal proceedings.